Government House, Barbados - (:unkn) unknown (My University, 2022)
The Government House of Barbados was built in 1702 and is the official residence of the Governor General of Barbados. It is located on Government Hill, St. Michael on lands that were once a Quaker plantation before being sold to the government of the day. The majestic colonial house sits at the end of a long driveway.
Landscape; Black and white; 7 x 9 inches. (print mounted on card)
Keywords: Official residences; Driveways; Houses; Historic buildings; Historic sites; Architectural elements; Heads of state; Historic houses; Government House